Bicarbonate rather than high pH in growth medium induced Fe-deficiency chlorosis in dwarfing rootstock quince A (Cydonia oblonga Mill.) but did not impair Fe nutrition of vigorous rootstock Pyrus betulifolia - Zhao, Yanyan; Chen, Yinglong; Liu, Songzhong; Li, Fei; Sun, Mingde; Liang, Zhenxu; Sun, Zhi; Yu, Futong; Rengel, Zed; Li, Haigang (Frontiers in Plant Science, 2023)
Quince A (Cydonia oblonga Mill.), a typical dwarfing rootstock in pear cultivation, is susceptible to iron (Fe) deficiency in calcareous soils. The aim of this study was to compare the strategies in Fe uptake and utilization in dwarfing rootstock quince A (low Fe efficiency) versus a typical vigorous rootstock Pyrus betulifolia (PB) with high Fe efficiency. Quince A and PB were grown in nutrient solution (pH 6.3) for 4 weeks followed by three pH treatments: pH6.3, pH8.3a (adjusted with hydroxide) and pH8.3b (adjusted with bicarbonate). The Fe uptake and utilization indicators of the rootstocks were assessed at the onset of chlorosis symptoms (after 58 days of treatments). In contrast to PB, quince A exhibited Fe deficiency chlorosis under bicarbonate (pH8.3b).Bicarbonate stimulated the root proton secretion, inhibited root growth and ferric chelate reductase (FCR) activity in both PB and quince A, whereas high pH without bicarbonate (pH8.3a) stimulated only root proton release. Both species accumulated more Fe in roots under high pH treatments than under pH6.3, resulting in Fe sufficiency in leaves. Both high pH treatments increased the activity of leaf FCR in PB and quince A. However, extractable Fe(II) concentration in leaves was increased by high pH treatments in PB only. This study demonstrated that depressed Fe(III) reduction in leaves caused by bicarbonate rather than high pH explained Fe deficiency in quince A grown in bicarbonate-containing medium.